Kontrol Motor AC 3 Fasa Pada Peluncur Peluru Kendali - Rosyidin Sufyani; Syafruddin R; Givy Devira Ramady; Andrew Ghea Mahardika; Decy Nataliana (Prosiding Seminar Nasional Teknoka, 2019)
The background of the research is the need for 3 phase ac servoposition is needed to obtain a precise position, where the 3 phase ac motor with a power between 0.25 to 1 kw when used to make precise position movements, is quite difficult, because of the moment of inertia, when silent governed the way the starting time process from zero speed to nominal speed is quite long, about 1 to 2 seconds, as well as when from normal rotation commanded to stop zero speed the process of stopping time ranges from 2 to 3 seconds, whereas we want starting time 0.5 seconds and stop time 0.75 seconds stop right in the position ordered. This problem is very disturbing in making other system controls, because the time is long enough in the starting time and stoping time, and this process will repeat every time according to the modulation of the control signal received by the motor switching system, while the operating time of the desired system is only 30 seconds in following the target so as not to disappear in the camera shot, starting from the target start is obtained until the end of the process when turning on the firing button, as used in controlling the missile launcher. The launcher's processing time is only about a few minutes, for searching, locking and firing, otherwise the object to be locked will disappear from observation.